2022
DOI: 10.3389/fphar.2022.1022266
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the efficacy and mechanism of action of panax ginseng monomer saponins treat toxicity

Abstract: As a traditional Chinese herbal medicine, Panax ginseng C. A. Meyer (PG) has preventive and therapeutic effects on various diseases. Ginsenosides are main active ingredients of PG and have good pharmacological effects. Due to the diversity of chemical structures and physicochemical properties of ginsenosides, Currently, related studies on PG monomer saponins are mainly focused on the cardiovascular system, nervous system, antidiabetic, and antitumor. There are few types of research on the toxin treatment, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…But it must be acknowledged that, like heavy metals, excessive concentrations of metal ions from the aforementioned metals can induce various forms of cellular damage and apoptosis, resulting in increased wound inflammation and oxidative stress responses (Song et al, 2019). According to previous reports, substances such as saponins [rhodioloside (Tang et al, 2021a), Panax ginseng saponin (Wang et al, 2022c)], polyphenols (Orlowski et al, 2018) have been shown to rescue different types of cell damage caused by metal ions. Xu's team (Xu et al, 2010) pointed out that ginsenoside Rg1 can inhibit the upregulation of divalent metal transporter 1/iron responsive element, reducing the lowering of mitochondrial transmembrane potential in MES23.5 cells, thereby alleviating iron-induced oxidative stress.…”
Section: Figure 10mentioning
confidence: 99%
“…But it must be acknowledged that, like heavy metals, excessive concentrations of metal ions from the aforementioned metals can induce various forms of cellular damage and apoptosis, resulting in increased wound inflammation and oxidative stress responses (Song et al, 2019). According to previous reports, substances such as saponins [rhodioloside (Tang et al, 2021a), Panax ginseng saponin (Wang et al, 2022c)], polyphenols (Orlowski et al, 2018) have been shown to rescue different types of cell damage caused by metal ions. Xu's team (Xu et al, 2010) pointed out that ginsenoside Rg1 can inhibit the upregulation of divalent metal transporter 1/iron responsive element, reducing the lowering of mitochondrial transmembrane potential in MES23.5 cells, thereby alleviating iron-induced oxidative stress.…”
Section: Figure 10mentioning
confidence: 99%